Case studies: A possible mechanism for F2-lacuna formation. Issue 11 (1st December 2019) - Yang, Shenggao; Zhang, Beichen; Liu, Yang; Zhu, Yaguang; Yang, Xu; Tian, Chao; Yue, Fulu; Xu, Peikang; Jiang, Jianming
Abstract: Two cases of F2-lacuna and their simultaneous ionospheric convection and TEC variations were presented to further understand F2-lacuna formation mechanism. Both cases of F2-lacuna are accompanied by decreased electron density and increased plasma flow. Through analyzing the role of convection electric field in the formation of F2-lacuna, an explanation for F2-lacuna formation was provided. The joule heating and frictional heating ascribed to the strengthened electric field causes the increase of electron and ion temperature, which subsequently, causes the enhancements of the recombination rate and the upflow of the O + density resulting in decreased O + density in F2 region.